On Generalized Holder’s Inequality in Weak Morrey Spaces - Wajih, Asyraf; Gunawan, Hendra (Journal of the Indonesian Mathematical Society, 2020)
In this paper we reprove generalized H"older’s inequality in weak Morrey spaces. In particular, we get sharper bounds than those in gunawan2. The bounds are obtained through the relation of weak Morrey spaces and weak Lebesgue spaces.